PERAWATAN KOMUNITAS AGREGAT USIA DEWASA DENGAN DIABETES MELITUS MENGGUNAKAN INTERVENSI DIABETES SELF-MANAGEMENT EDUCATION (DSME): Diabetes Self-management Education (DSME) - Nadya Nova, Mutiara; Tahlil, Teuku; Asniar (Yayasan Sagita Akademia Maju, 2024)
Diabetes mellitus requires long-term treatment, can cause complications that can be life-threatening and affect the lives of diabetes mellitus patients. Self-management actions include glucose management, diet control, physical activity, and the use of health care can minimize complications. Lack of knowledge can make self-management ineffective. This case study aims to apply a community nursing care through the implemention of Diabetes Self-Management Education (DSME) in adult population using flip sheets and leaflets. A community nursing assessment conducted on nine patients and a nursing diagnosis of the ineffective health self-management was established based on the assessment data. The nursing care plan was prepared and focused on health education about self-management of diabetes mellitus using flip sheets and leaflets. Before and after the implementation of nursing, tests were carried out using the Diabetes Self-Management Questionnaire (DSMQ). The evaluation results showed significant changes in self-management after the intervention (100% of respondents were in a good category). The average percentage increase in self-management status is 48.55%. The conclusion was that counseling for the aggregate of adults with diabetes mellitus positively influenced self-management status. It is recommended for community nurses to provide health education in the community, especially for adults with diabetes mellitus.